2022
DOI: 10.1111/ilr.12229
|View full text |Cite
|
Sign up to set email alerts
|

Networks of trust: Accessing informal work online in Indonesia during the COVID‐19 pandemic

Abstract: The author gratefully acknowledges the financial support provided by the Chancellor's International Scholarship for her doctoral study at the University of Warwick. She would like to thank the research participants for sharing their stories, and Dr Tzehainesh Teklè and three anonymous reviewers for their feedback and suggestions, which helped improve this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It identifies the frequency of two documents co-cited together by other documents (Culnan, 1987), which represents the similarity between the documents. This analysis used a Bellesia et al, 2019Bellesia et al, , 2023Mäntymäki et al, 2019;Aspers and Darr, 2022;Beigi et al, 2022;Hendl and Jansky, 2022;Octavia, 2022;Peng, 2022) 2 Labour process theory 5 (Gandini, 2019;Wu et al, 2019;Anwar and Graham, 2021;Aspers and Darr, 2022;Heiland, 2022) 3 Labour theory of value 3 (Anderson et al, 2016;Ekbia and Nardi, 2019;Gandini, 2019 Job demands-resources (JD-R) theory 1 (Nilsen and Kongsvik, 2023) Source: Data compiled by the authors co-citation threshold of ten documents to focus on the most influential publications in this area (Goyal and Kumar, 2021). The results show that 91 out of the 603 documents have been co-cited by other documents in the network at least 15 times.…”
Section: Co-citation Analysismentioning
confidence: 99%
“…It identifies the frequency of two documents co-cited together by other documents (Culnan, 1987), which represents the similarity between the documents. This analysis used a Bellesia et al, 2019Bellesia et al, , 2023Mäntymäki et al, 2019;Aspers and Darr, 2022;Beigi et al, 2022;Hendl and Jansky, 2022;Octavia, 2022;Peng, 2022) 2 Labour process theory 5 (Gandini, 2019;Wu et al, 2019;Anwar and Graham, 2021;Aspers and Darr, 2022;Heiland, 2022) 3 Labour theory of value 3 (Anderson et al, 2016;Ekbia and Nardi, 2019;Gandini, 2019 Job demands-resources (JD-R) theory 1 (Nilsen and Kongsvik, 2023) Source: Data compiled by the authors co-citation threshold of ten documents to focus on the most influential publications in this area (Goyal and Kumar, 2021). The results show that 91 out of the 603 documents have been co-cited by other documents in the network at least 15 times.…”
Section: Co-citation Analysismentioning
confidence: 99%
“…The informal economy has been one of the key drivers of digital transformation in Indonesia (Prasetyo, 2021), with many informal entrepreneurs having shifted online. While many previously self-employed people have signed up for ride-sharing and other digital labor platforms, others have successfully mobilized social media to market their products or services (Octavia, 2021). Influencers, as digital entrepreneurs, sometimes operate entirely informally, but at other times interact with the formal economy by endorsing registered businesses' products, or by playing a shady role in official electoral processes (Finery Report, 2020).…”
Section: Influencers and Their Subcultures In Indonesiamentioning
confidence: 99%
“…Similarly, Maffie's (2020) study of Uber riders Facebook groups found that workers use online spaces to share grievances and build collective identity, which in turn is associated with more positive views on unions and improved interest in joining a labour association. An emerging body of literature in several empirical contexts, such as Indian app-based cab drivers (Parth et al, 2021), Kenyan Uber workers (Anwar et al, 2022), Scottish on-demand food couriers (Gregory, 2021), and Indonesian platform-based domestic workers (Octavia, 2021) is providing insights into how digital communication spaces and social media groups enable collective processes of solidarity and workers' resistance to work around management's restrictive practices. Given the increasing prevalence of gig work, platform work, and crowdwork in the contemporary labour market, Netnographic research represent an indispensable methodology from which to empirically chart and understand collective identity construction, resistance and struggle in these otherwise inaccessible contexts.…”
Section: Gig Work and Precarious Workmentioning
confidence: 99%